A generalized strain energy density exhaustion model allowing for compressive hold effect. (November 2017) - Wang, Run-Zi; Zhu, Xu-Min; Zhang, Xian-Cheng; Tu, Shan-Tung; Gong, Jian-Guo; Zhang, Cheng-Cheng
Highlights: Energy density exhaustion model for creep-fatigue life prediction is extended. Mean stress effect is considered in the present model. A correction-factor of oxidation is used to describe oxidation damage. A three-dimensional creep-fatigue-oxidation interaction diagram is proposed. Abstract: The aim of the present work is to propose a generalized strain energy density exhaustion model to predict the creep-fatigue lives. The oxidation damage, which is described by a correction factor representing the non-linear oxidation damage mechanism, is considered in the proposed model. All the 77 experimental data sets of GH4169 superalloy at 650 °C, Inconel 738 superalloy at 850 °C and P91 steel at 550 °C in both tension-hold-only and compression-hold-only tests are used to validate the prediction capabilities of the model. The fatigue, creep and oxidation damages per cycle are separately calculated. Then a three-dimensional damage interaction diagram combined with a suitable enveloping surface is proposed.